Impact of Digital Financial Inclusion on Agricultural Enterprise Innovation - Li, Qian; Li, Xiaoning; Zhai, Qianqian; Li, Wei; Wagan, Shoaib Ahmed (Transformations In Business & Economics, 2025)
Innovation is an inexhaustible motive force for enterprise development, and the arrival of the digital economy era has injected new vitality into enterprise innovation and development. Whether agricultural enterprises can seize the opportunities of digital economy advancements for innovation remains to be further investigated. This study aims to reveal whether agricultural enterprises can enjoy the digital financial inclusion dividend and play a role in promoting innovation. Based on resource dependence theory and financing constraint theory, using the financial data of Chinese A-share listed agricultural enterprises and the digital financial inclusion data of the Institute of Digital Finance Peking University from 2011 to 2022, the impact of digital financial inclusion on agricultural enterprise innovation was empirically examined. The Results indicate that, (1) The development of digital financial inclusion can significantly promote the innovation of agricultural enterprises, among which the usage depth of digital financial inclusion exerts a stronger effect than its coverage breadth and digitalization level. This conclusion still holds after performing the endogeneity and robustness tests. (2) Compared with non-state-owned enterprises, and enterprises in the eastern region and small-sized enterprises, state-owned enterprises, as well as enterprises in the central and western regions, and large-sized enterprises are promoted more substantially in the aspect of innovation by digital financial inclusion. (3) Digital financial inclusion mainly promotes the innovation of agricultural enterprises by alleviating financing constraints and enhances investment guarantee for agricultural enterprises to continuously carry out innovative activities. The conclusions can provide theoretical guidance for agricultural enterprises to use digital financial inclusion to alleviate financing constraints, sustain innovation, and provide a decision-making basis for government to formulate innovation support policies for agricultural enterprises.